Critical reflections on introducing e-learning within a blended education context. (12th April 2019) - Laskaris, Dimitris; Heretakis, Emmanuel; Kalogiannakis, Michail; Ampartzaki, Maria
For three consecutive semesters (2014-2016), we conducted an action research project attempting for the first time to introduce in blended education context an e-course, in the Faculty of Communication and Media of Athens University. The first author constructed the e-course by utilising the open source learning management system - Moodle, the prototype model of digital learning called 'Interactive Evaluation' that was embodied in the design of the e-course and in the cycles of action research. The second author, whose notes and bibliography of the conventional course have been transformed to meet our social constructionist approach to distance learning, acted as critical friend for the research projects. This paper summarises our answers to the following questions: (1) How have we dealt with the 'expressed' interest of students? (2) What were the critical events that occurred during the course and how have we responded to them? (3) What are the factors that affected students' participation in the various modules of the e-course? Our intention is to explore the ways in which the management of the e-courses has come to interconnect with built pedagogy through the implementation of interactive evaluation.